Revitalisasi Etika Sosial-Politik dalam Hidup Berdemokrasi - Mali, Mateus (Jurnal Orientasi Baru, 2011)
Discussion on social-political ethics brings us to understand that democraticsystem has to give space for the peopleâ€™s participation when a public policy istaken. Democracy or â€œgovernment by and for the peopleâ€ requires some form ofrepresentation and must bring the people to the welfare society. Welfare society isnot only how to fulfill the basic needs of the people but also how to empower theconducive interaction and relationship among them. For this reason, democracytakes freedom and justice to be the basic ideal for living together. Freedom andjustice will grow the personal responsibility in a society. This essay is an attemptto revive the importance and the essence of a democratic system in our societynowadays.